The Cognitive Development of Children with Speech Delayed - Fahdin, Risma Galuh Pitaloka ((JELE) Journal Of English Language and Education, 2020)
The goal of this study is to know about speech delay. Children with speech delay feel difficult to communicate and understand others. The study is about types of speech delay, the correlation between cognitive development and speech delay on children, bilingual children that suspicioned have speech delay, also resolve the problems need to understand how to handle children with speech delay with special treatment and how to teach English for children with special needs education. This study is based on library research which takes materials from previous research. There are some types of speech delay but this study discussed one type of speech delayed which caused by lack of vocabulary. Speech delay will affect children’s life because communication is important. Since this research contains one type of speech delay, better in the next research can discuss all types of speech delay deeply and the solutions to face it.